2015
DOI: 10.1556/2006.4.2015.029
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder risk, exercise dependence, and body weight dissatisfaction among female nutrition and exercise science university majors

Abstract: Background and AimsPast research has examined eating disorder risk among college students majoring in Nutrition and has suggested an increased risk, while other studies contradict these results. Exercise Science majors, however, have yet to be fully examined regarding their risk for eating disorders and exercise dependence. Based on pressures to fit the image associated with careers related to these two disciplines, research is warranted to examine the potential risk for both eating disorder and exercise depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 22 publications
5
36
2
2
Order By: Relevance
“…In addition, there were no differences among academic majors in either the EAT-26 subscales (i.e., dietary restraint, binge eating behavior, and oral control level) or the TFEQ-R18 subscales (i.e., cognitive restraint, loss of control, and emotional eating). These findings are in agreement with some studies [17,18,39], in which students in nutrition major were neither at higher risk of eating disorder nor differed in subscale behaviors, compared to students in other majors. This is inconsistent, however, with other studies, in which female nutrition and dietetics students had higher levels of disordered eating attitudes and behaviors (EAT-26 scores) compared to other first year program students [15], and nutrition students showed higher levels of dietary restraint than non-nutrition students [12,14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, there were no differences among academic majors in either the EAT-26 subscales (i.e., dietary restraint, binge eating behavior, and oral control level) or the TFEQ-R18 subscales (i.e., cognitive restraint, loss of control, and emotional eating). These findings are in agreement with some studies [17,18,39], in which students in nutrition major were neither at higher risk of eating disorder nor differed in subscale behaviors, compared to students in other majors. This is inconsistent, however, with other studies, in which female nutrition and dietetics students had higher levels of disordered eating attitudes and behaviors (EAT-26 scores) compared to other first year program students [15], and nutrition students showed higher levels of dietary restraint than non-nutrition students [12,14].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported different tendency for abnormal eating behaviors or body concerns between health-related non-nutrition majors and nutrition major [19,39]. Therefore, current study distinguished these two groups and included three academic major groups.…”
Section: Methodsmentioning
confidence: 99%
“…From a public health perspective, little is known about the relationship between suicide risk and symptoms of eating disorders, in the college setting or otherwise. This population‐level study of a large, random sample of students is an important compliment to previous research, which has focused primarily on clinical samples or specific subsets of students, such as female athletes or sorority women (Allison & Park, ; Harris et al, ; Wollenberg et al, ). This study drew from a large sample of college students on campuses across the United States to assess risk of suicidality along a continuum of eating disorder symptomatology, examining symptom severity, weight and shape concerns, and specific behaviors of binging and purging.…”
Section: Discussionmentioning
confidence: 91%
“…From a public health perspective, little is known about the relationship between suicide risk and symptoms of eating disorders, in the college setting or otherwise. This population-level study of a large, random sample of students is an important compliment to previous research, which has focused primarily on clinical samples or specific subsets of students, such as female athletes or sorority women (Allison & Park, 2004;Harris et al, 2015;Wollenberg et al, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…*p = 0.001. Psychology some of them only considering women, others women and men and sometimes contrasting the findings with other careers as a comparison group (Crockett & Littrell, 1985;Torresani, 2003;Cruz et al, 2008;Laus, Moreira, & Costa, 2009;Chávez-Rosales, Camacho Ruiz, Maya Martínez, & Márquez Molina, 2012;Kolka & Abayomi, 2012;Mealha, Ferreira, Guerra, & Ravasco, 2013;Meza Peña & Pompa Guajardo, 2013;Nergiz-Unal, Bilgic, & Yabanci, 2014;Harris et al, 2015). However, it is still unclear whether the presence of BD and EDs symptoms were present before entering to the career or developed as a result of the knowledge and skills learned during the course of their professional preparation.…”
Section: Discussionmentioning
confidence: 99%